Offset-dependent reflectivity : theory and practice of AVO analysis - Backus, Milo M., 1932-; Castagna, John Patrick (Society of Exploration Geophysicists, 1993)
Recognizing the need for education and further research in AVO, the editors have compiled an all-encompassing treatment of this versatile technology. In addition to providing a general introduction to the subject and a review of the current state of the art, this unique volume provides useful reference materials and data plus original contributions at the leading edge of AVO technologies.
Keywords: Petroleum -- Prospecting.; Natural gas -- Prospecting.; Amplitude variation with offset analysis.; elektronické knihy; electronic books